Glue embolization of a pial arteriovenous fistula of the spinal artery - Doniselli, Fabio Martino; Paolucci, Aldo; Conte, Giorgio; Rampini, Paolo; Arrichiello, Antonio; Triulzi, Fabio Maria (Acta Biomedica Atenei Parmensis, 2020)
There are no clear guidelines about the treatment Pial Arteriovenous Fistulae (PAVF). For high-risk and severally symptomatic fistulae surgery is the first choice of treatment, including feeding artery ligation, surgical resection, radiosurgery and endovascular embolization techniques. We described a case of a patient with a symptomatic PAVF at the craniocervical junction fed by the anterior spinal artery, successfully treated with endovascular approach consisting of glue embolization of the feeding vessel.